The Effect of Human Resource Management Strategies on Employee Welfare at Bank Jateng - Rosidah Firnanda; Muafi (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to explore the influence of human resource management (HRM) strategies on employee well-being at PT Bank Pembangunan Daerah Jawa Tengah (Bank Jateng). Using a qualitative exploratory-descriptive approach, data were collected through in-depth interviews, observations, and documentation of the company's annual report. The results indicate that Bank Jateng has successfully built a robust well-being ecosystem through an integrative HRM strategy, which positions employees as human capital. The main strategies implemented include internalizing the